AN ANALYSIS OF VERBAL PHRASE ERROR IN BRITISH PARLIAMENTARY DEBATE BY THE MEMBERS OF ENGLISH DEBATING SOCIETY OF TIDAR UNIVERSITY IN THE ACADEMIC YEAR 2015/2016 - Anggi Ayu Risanti; Dwi Winarsih; Lilia Indriani (Faculty of Education and Teachers Training, 2018)
Tidar University provides the subject of English to be learned not only by those who study in English Department, but for all students of those five faculties. However, not all students who learn English in Tidar University have outstanding English skills. In doing the debate, sometimes they use Indonesian patterns to construct English sentence. There are two objectives of this research; the first is to know the types of verbal phrase error made by the members of English Debating Society in Tidar University in British Parliamentary Debate. The second is to know the causes of verbal phrase errors of the members of English Debating Society by analyzing their utterances. The subject of the study is the members of English Debating Society who are the students of Tidar University in the academic year of 2015/2016. There were 8 members doing British Parliamentary Debate in 4 groups. Having collected data, the writer analyzed the data by identifying the errors, classifying the types of errors, discussing the causes of verbal phrase errors, and analyzing the verbal phrase errors by using descriptive qualitative method. After conducting the data analysis, the writer finds that common errors of verbal phrase made by the students are as follows: addition 20%, omission 21.54% and miss-formation 58.46%. In general, these errors are caused by 24.62% ignorance of rule restriction, 20.77% incomplete application of rule, and 54.61% false concept hypothesized. Finally, the writer concludes that the ability of the members of English Debating Society in using verbal phrase is still low.